The Influence of Transformational Leadership and Organizational Culture on Employee Job Satisfaction and Work Productivity at PT. Asuransi Jiwa Sinarmas MSIG Life Cab. Lombok - Nensi Anggraini; Abdul Azis Bagis; I Nyoman Nugraha (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the influence of transformational leadership and organizational culture on employee productivity, with job satisfaction serving as a mediating variable at PT. Asuransi Jiwa Sinarmas Msig Life Cab. Lombok. The research employed a quantitative approach with an associative causal design using a survey method, in which data were collected through the distribution of questionnaires to all respondents comprising the research population of 56 employees. The research instruments covered the variables of transformational leadership, organizational culture, employee productivity, and job satisfaction, each measured using several indicators that were tested for validity and reliability. Data analysis was conducted using SmartPLS 3.0 to examine both direct and indirect relationships among variables. The results indicate that transformational leadership and organizational culture have a positive and significant effect on employee productivity. Furthermore, transformational leadership and organizational culture also exert a positive and significant influence on job satisfaction. Job satisfaction, in turn, has a positive and significant effect on employee productivity. In addition, job satisfaction significantly and positively mediates the relationship between transformational leadership and organizational culture and employee productivity. The coefficient of determination demonstrates that employee productivity is strongly explained by the variables examined in this study.